Effect of sequential kicks on programming time and movement time in taekwondo - Chen, C.; Yu, C.; Chen, T.; Su, T. (Journal of Human Kinetics, 2025)
It is a critical tactic in combat sports to launch consecutive attacks that consist of two or more individual kicks strung together in time. The study aimed to assess how the number of round kicks would impact reaction time (RT) and movement time (MT). Twenty-eight experienced taekwondo athletes performed one of four different kick responses randomly in a simple RT paradigm: 1) clenched lead fist without a kick (task A); 2) round kick following task A (task B); 3) double kick following task B (task C); and 4) turning kick following task C (task D). Electromyography recordings from the thenar muscle and acceleration impulses from a triaxial accelerometer positioned at the heavy bag were used to determine premotor time and kick time, respectively. Repeated-measures ANOVA revealed that task B, task C, and task D significantly increased RTs (p < 0.001). The RT of task D was longer than that of task B and task C (p < 0.001). The movement time of the round kick in task C and task D was longer than in task B (p < 0.001). The movement time of the double kick in task D was longer than in task C (p = 0.003). Additional time is required to prepare for multi-kicks responses. An increased number of individual kicks to execute as a whole may slow down the kick movement.